Let's say Als frog jumped x inches Fred's frog jumped 7x inches 7x + x = 56 8x = 56 x = 7 Fred's frog = 7x = 7* 7 = 49 inches

Let's say Als frog jumped x inches Fred's frog jumped 7x inches 7x + x = 56 8x = 56 x = 7 Fred's frog = 7x = 7* 7 = 49 inches

How many students created each item (answer)

Number of students creating a dessert = d Number of students creating an appetizer = d + 7 Number of students creating two dishes = total number of students - total number creating single dish = 50 - (d+d+7) = 50 -(2d+7) According to the problem the above is...

5/3d-3/2=-1/2 (answer)

Moving -3/2 to the other side of the equals sign changes the -ve sign to a +ve 3/2 (5/3)d = -1/2+3/2 (5/3)d = 1 d = 1/(5/3) = 3/5

Number of seagulls in the flock now = 1/3 * 12 = 4 seagulls Number of ducks -= 12 - 4 = 8 ducks Let x be the new seagulls that should join the flock to make the ratio change to 19:8 Total number of birds = x+12 Total number of seagulls = x+4 , since all the birds that...

Wats n-3/8=1/8 (answer)

Add 3/8 on both sides n - 3/8 + 3/8 = 1/8 +3/8 Therefore, n = 1/8 + 3/8 = (3+1)/8 = 4/8 = 1/2

X2- 8x + 3x - 24 =0 x(x-8) +3(x-8) = 0 (x+3) (x-8) = 0 x = -3, 8 answer c.

x = sqrt (4) x = +2 , - 2 answer a.

= -2^4 x^3 y^6/(-2^2 x^-2 y^-3) = -2(4-2) x(3+2) y(6+3) = -22 x5 y9 = 4x5 y9 Answer d.

factor x squared-7x-30 completely (answer)

X2-10X+3X-30 = X(X-10)+3(X-10) = (X-10) (X+3)

y = -3x-6 comparing the above line in the form: y = mx +c m = -3 The equation of the line perpendicular to the above line will have the slope m = 1/3 ( opposite reciprocal) so the equation of the line passing through ( -1, 5) using the slope intercept form...

Word problem Algebra problem (answer)

a) l (brightness) = 19/ (4 * 22) watt per sq. meter The brightness/intensity of the light varies inversely to the distance you are from the source of light, if d is increased to 3 meters for example, the brightness decreases even further. b) The sum of the intensities of...

(2.5x 103) (4.2 x 102) = (2.5 x 4.2) x ( 103+2 ) = 10.50 x 105 Answer is c.

(3x2/5y3)-2 = 1/(3x2/5y3)2 = (5y3)2/(3x2)2 = 25y6/9x4 Answer is d.

(4x2y3 ) (5x-3 y-2 z0) Rearranging, = (4*5) x(2-3) y(3-2) (1) Note: z0 = 1 = 20 x-1y = 20y/x Could you please check d., Appears to be a typo.

Find the general solution? (answer)

Find the homogeneous solution first by writing the characteristic equation: r^4 - 1 = 0 (r^2 + 1) ( r^2-1) = 0 r = 1, -1, i, -i The homogeneous solution is of the form: yh = c1et + c2 e-t + c3 cos(t) + c4 sin (t) Particular solution can be solved in 2 steps...

if you have a bunch of points represented as (x,y) and if you are able to plot the points on a graph and connect all the lines using a straight line using a scale, you can say the relationship is linear. for ex: speed of travel (x-axis) ...

4y-x=27 2x+7y=21 (answer)

Multiply this equation by 2 : [4y-x=27] x 2 we are multiplying by 2 so that -2x and +2x cancel each other out and we can solve for one of the unknowns y. The trick here is to somehow solve for one unknown first 8y-2x = 54 Now, rearrange and solve for unknowns -2x +8y = 54 2x ...

Please try integrating using partial fractions; factorize the denominator first.

what is x+2 =8 (answer)

I think the curly bracket { is a modulus written like | Questions of this type will have two solutions as indicated in the solution choices. Remember that modulus changes negative to positive values. 1st solution: put a negative sign around (x+2) and solve -(x+2) =...

Linda W.

Reading should be fun and an adventure!

New York, NY

4.9
(296 ratings)

Daisy C.

Effective ELA Tutor - Boston College Graduate - Masters Degree ELA/ESL

Atlantic Beach, NY

5.0
(131 ratings)